Framework for Colorectal Cancer Health Needs Assessment in North and Central Asian Countries - Pratiti, Rebecca (International Journal of Innovative Research in Medical Science, 2021)
Colorectal cancer (CRC) is the third leading cause for cancer worldwide. Prevalence of CRC is increasing in North and Central Asian Countries (NCAC). European guidelines encourage member countries to allocate resources for primary prevention of CRC through screening. Though, cost-effective screening is becoming a priority. A framework for health priority determination to prioritize CRC screening was developed. Public health websites were accessed to abstract epidemiologic data. The framework included prioritization by absolute risk (incidence, prevalence), relative risk (CRC ranking for national cancer deaths) and population attributable risk for the disease. Risk indicators were identified for the NCAC. Further detailed risk assessment scoring was completed to assess the CRC disease burden. Statistical analysis was performed for correlation. Variables included in risk assessment were population, life expectancy, gross national income per capita, percent GDP spent on health expenditure, total expenditure on health per capita, age standardized mortality to incidence ratio, cancer ranking by incidence and smoking prevalence. Risk assessment showed Kyrgyzstan, Georgia, Belarus and Armenia have more than expected CRC burden. Tajikistan, Turkmenistan and Latvia have lower than expected CRC burden. Conclusion: Identifying high CRC burden countries to prioritize screening is important. Uniform and comparable CRC risk indicators for the region is needed. Health need assessment and priority setting is important for better distribution of resources. Countries with lower risk score may implement preventive policy to reduce CRC risk factors and countries with higher risk could adapt mitigating policy for early diagnosis of CRC.